FIRM VALUATION CONCEPT AND DISCOUNTED CASH FLOW METHOD: A COMPARISON OF STOCK MARKETS - BASCI, Esref Savaş (Annals of Spiru Haret University. Economic Series, 2019)
Company (or firm) valuation – an evaluation process of a company to appreciate the value of a company’s right in this company or business. There are two objective and subjective aspects of value. The subjective value is the value determined by individuals and desires. For example, it is a subjective decision that the investor assesses the competitor over the normal to be monopoly in the market. The objective value is the value determined by the cost and benefits of the goods and services. Although there are many performance measures that measure company success, none is as comprehensive as value. There is a strong and linear relationship between a company’s market value and its discounted cash flows. Because earnings are used to generate the income statement, they cannot be used to measure cash flows. Firm valuation means seeking the goal of the firm which is listing it on the Stock Exchange. Real value of the firm can be calculate with different methodologies. These methods are related to future expectations or background of the firm’s financial data. Discounted Cash Flow (DCF) Method is one of the firm valuation methods used all around the world and it is accepted by the experts. Market value is also used for comparison and performance measurement purposes. Valuation of a company’s future expectations, current status, mergers or acquisitions is extremely important. Even the firm value can be used to compare the capital markets of countries. In our study, capital markets and total market values of selected countries are compared. The increase in the share price increases the market value of the company. Therefore, the aim of the firms should be to increase the shareholder value or to take decisions to increase the stock price.